Perjuangan antologi puisi dan cerpen remaja - Hassan Alias; Adnan Abd. Jamil (Dewan Bahasa dan Pustaka, 1996)
Prize winning juvenile poems and short stories of the 1995 Bank Rakyat Student Literary Award.